This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.

When posting on Brilliant:

Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .

Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.

Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.

Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

Markdown

Appears as

*italics* or _italics_

italics

**bold** or __bold__

bold

- bulleted - list

bulleted

list

1. numbered 2. list

numbered

list

Note: you must add a full line of space before and after lists for them to show up correctly

Hi, if we substitute $k = a^2 + b^2 + c^2$ into the inequalities, then the system of inequalities is homogeneous, let $u = a + b + c$, $v = ab + bc + ca$ and $w = abc$, then the system becomes $\frac{2w}{\sqrt{u^2 - 2v}} - \sqrt{2u^2 - 4v} \leq u \leq \frac{2w}{u^2 - 2v} + \sqrt{2u^2 - 4v}$ i.e. $\frac{2w}{\sqrt{u^2 - 2v}} - \sqrt{2u^2 - 4v} - u \leq 0 \leq \frac{2w}{u^2 - 2v} + \sqrt{2u^2 - 4v} - u$ Both expressions are linear in $w$. By $uvw$ method it suffices to prove inequality in two cases 1) $(a - b)(b - c)(c - a) = 0$, 2) $abc = 0$, in the first case we let WLOG $b = c$ and we have to prove $\frac{2ab^2}{a^2 + 2b^2} - \sqrt{2a^2 + 4b^2} \leq a + 2b \leq \frac{2ab^2}{a^2 + 2b^2} + \sqrt{2a^2 + 4b^2}$ which is easy. In the second case WLOG let $c = 0$ and we have to prove $-\sqrt{2a^2 + 2b^2} \leq a + b \leq \sqrt{2a^2 + 2b^2}$ which is again easy.

Here is link to the method used: PDF I used different substitution, but it doesn't interfere with the method.

Good solution. Your main observation is that the inequality is equivalent to showing that $\left[ (a+b+c)(a^2+b^2+c^2) - 2abc \right]^2 \leq 2 (a^2+b^2 + c^2 )^3.$

This could also be done through brute force expansion and then AM-GM several times (i.e. Muirhead).

Great solution. Just to state that $2bc \leq b^2+c^2 < k$ since $a$ cannot be zero otherwise all of them are 0, which contradicts the condition $k>0$, just showing this so we do not need the $\frac{k}{3}$ thing.

for 3 real numbers a,b and c, notice that AM=(a+b+c)/3, GM=(abc)^(1/3) and RMS=sqrt[(a^2+b^2+c^2)/3].
try to use RMS>AM>GM.i tried and it worked.but the solution is around 20-22 lines long.so will take a long time to type :-(

Wow that is so long. You did it great. But I think for this problem, $AM - GM$ has nothing to do here. Like what David say, $AM - GM$ only works on positive number. Let say for your case $a = 1, b = -1$ and $c = 0$ then $AM = 0 < GM = \sqrt[3]{2}.$

Clearly the leftmost side is less than the rightmost side as $k$ is positive. But beyond that, I'll have to do more than a first time glance to get this!

Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in`\(`

...`\)`

or`\[`

...`\]`

to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestHi, if we substitute $k = a^2 + b^2 + c^2$ into the inequalities, then the system of inequalities is homogeneous, let $u = a + b + c$, $v = ab + bc + ca$ and $w = abc$, then the system becomes $\frac{2w}{\sqrt{u^2 - 2v}} - \sqrt{2u^2 - 4v} \leq u \leq \frac{2w}{u^2 - 2v} + \sqrt{2u^2 - 4v}$ i.e. $\frac{2w}{\sqrt{u^2 - 2v}} - \sqrt{2u^2 - 4v} - u \leq 0 \leq \frac{2w}{u^2 - 2v} + \sqrt{2u^2 - 4v} - u$ Both expressions are linear in $w$. By $uvw$ method it suffices to prove inequality in two cases 1) $(a - b)(b - c)(c - a) = 0$, 2) $abc = 0$, in the first case we let WLOG $b = c$ and we have to prove $\frac{2ab^2}{a^2 + 2b^2} - \sqrt{2a^2 + 4b^2} \leq a + 2b \leq \frac{2ab^2}{a^2 + 2b^2} + \sqrt{2a^2 + 4b^2}$ which is easy. In the second case WLOG let $c = 0$ and we have to prove $-\sqrt{2a^2 + 2b^2} \leq a + b \leq \sqrt{2a^2 + 2b^2}$ which is again easy.

Here is link to the method used: PDF I used different substitution, but it doesn't interfere with the method.

Log in to reply

It took me a bit longer to understand, but I got it. Thanks :)

Log in to reply

Here's my solution:

Without loss of generality, assume that $|b|\leq |c|\leq |a|$. Then by $Cauchy - Schwarz$ Inequaility we have

$\begin{aligned} \left(a+b+c-\frac{2}{k}abc\right)^2 &= \left[a\left(1-\frac{2}{k}bc\right) + (b+c)\right]^2 \\ &\leq [a^2+(b+c)^2]\left[\left(1-\frac{2}{k}bc\right)^2 +1^2\right]\\ &= (k + 2bc) \left(2 - \frac{4}{k}bc +\frac{4}{k^2}b^2c^2\right) \\ &= 2k +\frac{8}{k^2} b^3c^3 - \frac{4}{k}b^2c^2\\ &= 2k +\frac{4}{k^2}b^2c^2(2bc - k) \end{aligned}$ Since $|b|\leq |c|\leq |a|$, $a^2 \geq\frac{k}{3}$, which implies that $\begin{aligned} 2bc \leq b^2 + c^2 = k - a^2 \leq k - \frac{k}{3} \leq \frac{2k}{3}< k \end{aligned}$ Therefore, $2bc - k < 0$, which yields $\left(a+b+c-\frac{2}{k}abc\right)^2 \leq 2k$ or $\begin{aligned} \frac{2}{k}abc - \sqrt{2k}\leq a+b+c\leq \frac{2}{k}abc +\sqrt{2k} \end{aligned}$

Log in to reply

Good solution. Your main observation is that the inequality is equivalent to showing that $\left[ (a+b+c)(a^2+b^2+c^2) - 2abc \right]^2 \leq 2 (a^2+b^2 + c^2 )^3.$

This could also be done through brute force expansion and then AM-GM several times (i.e. Muirhead).

Log in to reply

Great solution. Just to state that $2bc \leq b^2+c^2 < k$ since $a$ cannot be zero otherwise all of them are 0, which contradicts the condition $k>0$, just showing this so we do not need the $\frac{k}{3}$ thing.

Log in to reply

Hands down, your solution answered it all. Thanks :)

Log in to reply

for 3 real numbers a,b and c, notice that AM=(a+b+c)/3, GM=(abc)^(1/3) and RMS=sqrt[(a^2+b^2+c^2)/3]. try to use RMS>AM>GM.i tried and it worked.but the solution is around 20-22 lines long.so will take a long time to type :-(

Log in to reply

Wow that is so long. You did it great. But I think for this problem, $AM - GM$ has nothing to do here. Like what David say, $AM - GM$ only works on positive number. Let say for your case $a = 1, b = -1$ and $c = 0$ then $AM = 0 < GM = \sqrt[3]{2}.$

Log in to reply

How do you account for the fact that a,b, and/or c could be negative numbers too. I thought AM-GM only works for positive numbers.

Log in to reply

easy

Log in to reply

Would you like to show your solution or maybe some hints?

Log in to reply

Put the value of $k$ in both sides, square up, rearrange & you will get it after some reasoning...

Log in to reply

What do you mean by put the value of $k$ in both sides? Since there are three sides on the ineq.

Log in to reply

Any chance you could tell us where you got this problem?

Log in to reply

Oh sorry, my friend gave me this problem. Unfortunately she didn't mention where she get this problem from.

Log in to reply

That's fine, thanks. :)

Log in to reply

Clearly the leftmost side is less than the rightmost side as $k$ is positive. But beyond that, I'll have to do more than a first time glance to get this!

Log in to reply

Yes, and to be honest I don't have any clue to solve this inequality.

Log in to reply